HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN DAYA LEDAK OTOT LENGAN TERHADAP AKURASI SMASH BOLA VOLI DALAM KEGIATAN EKSTRAKURIKULER SISWA SMA NEGERI 2 RAMBAH HILIR - Tubagus, Satria; Zainur, Zainur; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract, The background of the problem in this study was that the results of the volleyball smash conducted by students SMA 2 Rambah Hilir were not optimal. This problem can be seen from the observations of researchers during extracurricular activities and also during the competition, this was allegedly due to the explosive muscle power factor of the limbs and the explosive strength of the arm muscles of the students State High School 2 Rambah Hilir. Therefore, the purpose of this study is to find out whether there is a relationship between leg muscle explosive power and arm muscle explosive power on the accuracy of volleyball smashes in extracurricular activities of students SMA 2 Rambah Hilir. This type of research is correlational comparing the results of measuring two different variables in order to determine the level of the relationship between these variables. As independent variable (X1) is limb muscle explosive power, (X2) arm muscle explosive power while dependent variable (Y) is accuracy of volleyball smash. The data of this study were obtained from the results of tests using vertical jump, two hand medicine ball put, and the accuracy of volleyball smash tests. The sample in this study were 12 high school students from Rambah Hilir, totaling 12 people (total sampling). Based on the results of the study it can be concluded as follows: From the results obtained by explosive limb muscle power has an insignificant relationship with the accuracy of the volleyball smash of SMA Negeri 2 Rambah Hilir, indicated by the results obtained, namely r count 0.04> r table 0.632. From the results obtained by arm muscle explosive power has a significant relationship with the accuracy of volleyball smash of SMA Negeri 2 Rambah Hilir students, indicated by the results obtained, namely rcount 0.96> r table 0.632. Thus, there is a significant relationship between the explosive strength of limb muscles and the explosive power of the arm muscles towards the accuracy of volleyball smashes in extracurricular activities of students in Rambah Hilir 2 High School, this is indicated by the results obtained by Rhitung 0.96> Rtable 0.632.Key Words: Explosive Power, Leg Muscles, Arm Muscles, Volleyball Smash Accuracy